2020
DOI: 10.1002/mnfr.201900921
|View full text |Cite
|
Sign up to set email alerts
|

Specificity, Dose Dependency, and Kinetics of Markers of Chicken and Beef Intake Using Targeted Quantitative LC‐MS/MS: A Human Intervention Trial

Abstract: Scope Common methods for food intake assessment are error‐prone. Estimating food intake via metabolite biomarkers in blood/urine is challenged by inter‐individual variation. Here, meat intake markers based on criteria defined within the FoodBAll consortium, including dose dependency, specificity, kinetics, and their ability to predict meat dose, are evaluated. Methods and results In two randomized human interventions, meat at different doses are consumed. Plasma concentrations of 100 analytes, including previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…A short-term (15 days) randomized crossover study showed that high red meat diet (420 g day −1 ) increased urinary TMAO when compared to vegetarian diets; however, no difference in TMAO was observed between a low meat diet (60 g day −1 ) and vegetarian diet. 85 In an intervention nutritional trial focused on various defined doses of meat (either chicken or beef ) following a crossover design, TMAO was the only analyte that increased after beef intake (but not after chicken intake) and remained above baseline even after 24 h. 86 Moreover, after the ingestion of 0, 100, or 200 g beef, clear dose-response was observed for TMAO levels, with maximum plasma concentrations around 11 h after the intake. Similarly, in a randomized controlled crossover trial, the effect of 4-weeks intake of red meat, poultry, and non-meat protein sources as 25% of their daily calories, was investigated, 87 and it was observed that compared to the white meat or non-meat diets, increased plasma and urine levels of TMAO occurred after consumption of the red meat diet.…”
Section: Reviewmentioning
confidence: 99%
“…A short-term (15 days) randomized crossover study showed that high red meat diet (420 g day −1 ) increased urinary TMAO when compared to vegetarian diets; however, no difference in TMAO was observed between a low meat diet (60 g day −1 ) and vegetarian diet. 85 In an intervention nutritional trial focused on various defined doses of meat (either chicken or beef ) following a crossover design, TMAO was the only analyte that increased after beef intake (but not after chicken intake) and remained above baseline even after 24 h. 86 Moreover, after the ingestion of 0, 100, or 200 g beef, clear dose-response was observed for TMAO levels, with maximum plasma concentrations around 11 h after the intake. Similarly, in a randomized controlled crossover trial, the effect of 4-weeks intake of red meat, poultry, and non-meat protein sources as 25% of their daily calories, was investigated, 87 and it was observed that compared to the white meat or non-meat diets, increased plasma and urine levels of TMAO occurred after consumption of the red meat diet.…”
Section: Reviewmentioning
confidence: 99%
“…Most analytes showed a correlation coefficient of at least 0.2, except for π‐methylhistidine, anserine, choline, and carnosine (Figure S1; Table S1). The diet strongly influences these four analytes 16 . π‐methylhistidine and its precursor anserine were described as markers for the intake of poultry meat.…”
Section: Resultsmentioning
confidence: 99%
“…The diet strongly influences these four analytes. 16 πmethylhistidine and its precursor anserine were described as markers for the intake of poultry meat. In contrast, τmethylhistidine, an endogenously produced compound released upon protein breakdown, displayed a high correlation between the samples from both days (π-methylhistidine p = 0.16; R 0.07; τmethylhistidine p < .001; R 0.07; Figure S2).…”
Section: Robustness Of Plasma Metabolite Concentrations In the Fastin...mentioning
confidence: 99%
“…Secondly, a priori-defined food biomarkers that have reached an appropriate level of validation [ 124 ] could be measured in association with CRF to test specific diet exposure-CRF hypotheses. For example, biomarkers of coffee (quinate, 3-hydroxypyridine sulfate, 1,3-dimethylurate), alcohol (ethyl glucuronide), multivitamins (pantothenate (B 5 ), pyridoxal, alpha-tocopherol) and citrus fruits (proline betaine) have been validated in large-scale cohort studies and subsequently tested in acute dietary intervention or feeding studies [ 116 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ]. Leveraging nutritional metabolomics data derived from other types of biospecimens (e.g., fecal metabolites) may also provide novel insights, such as diet-microbiome interaction in relation to CRF.…”
Section: Challenges Of Nutritional Metabolomics In Cancer-related Fat...mentioning
confidence: 99%